USE OF COMBINED ANTITUSSIVE MEDICATIONS IN PEDIATRICS - E.A. Vishneva; R.M. Torshkhoeva; Yu.G. Levina; A.A. Alekseeva; A.Yu. Tomilova; K.S. Volkov (Union of pediatricians of Russia, 2010)
Coughing is the most frequent symptom that accompanies diseases of the bronchopulmonary system. However, it may develop in a number of diseases that vary in its pathogenesis and location. Despite the variety of potential causes, in most cases acute respiratory infections (ARIs) play the key role in the etyology of coughing. Key methods of therapy for coughing in ARIs include efforts to improve the bronchial drainage function, restore mucociliary clearance, antiinflammation and, if necessary, broncholytic therapy. However, if coughing disrupts the well-being and condition of a patient (non-productive, short, compulsive, vomitory, chest pain causing, sleep and appetite disturbing), cough suppressive medications are administered. To this end, combined preparations containing codeine are successfully used in pediatric practice. Key words: coughing, combined antitussive preparations, children.(Pediatric Pharmacology. - 2010; 7(6):78-80)